Decoding intrathecal immunoglobulins and B cells in the CNS: their synthesis, function, and regulation: Modulation of immune responses mediated by different B cells is a potential therapeutic approach toward ameliorating several CNS disorders. (3rd March 2020) - Negi, Neema; Das, Bimal K.
Abstract: The discovery of an active lymphatic system in the meninges (dura mater) has opened up a wide range of possibilities for the role of CNS immunoglobulins in brain development in early fetal life or during infancy. The antibody-dependent and -independent functions of B cells in the immunopathogenesis of multiple sclerosis are not new to immunologists, yet their role in other neurodegenerative disorders such as Alzheimer's and Parkinson's disease is incompletely understood. Deep cervical lymph nodes have emerged as a candidate site for autosensitization against CNS antigens and have been shown to provide the right kind of milieu for the dynamic interaction of antigen-presenting cells, B cells, and T cells. The presence of different B cells in the lymph nodes and the production of natural autoantibodies by B-1 cells have definitely unlocked another piece of the puzzle. At a time when CD19 and CD20 monoclonal antibodies have shown remarkable results in ameliorating the relapse and progression of multiple sclerosis, it is imperative to dissect out the diversity in B cell populations inside the CNS to identify new targets to improve current treatment regimens for neurodegenerative diseases. This review highlights the origin, migration, function, and regulation of B cells and the production of intrathecal immunoglobulins considering the previous and current findings and taking into account the differences between a healthy state and the changes that occur during an inflammatory or autoimmune response.